Application of new technology data acquisition using aerial (UAV) digital images for the needs of urban revitalization - Banaszek, Anna; Zarnowski, Aleksander; Cellmer, Anna; Banaszek, Sebastian (International Conference “Environmental Engineering”, 2017)
The municipal authorities are responsible for carrying out relevant, objective analysis of areas for revitalization, identifying problems and barriers, diagnosis of the causes and determiningthe appropriate range of activities. From the point of view of urban regeneration one of the key issues is to obtain timely and reliable geospatial data. The article presents the possibility of using digital images obtained from the UAV platform to support the urban regeneration process. As part of the research work involving an inventory of urban space one made photogrametry flights with UAVs DJI Inspire One. Data processing software that was used is Pix4D and QGIS. The results allow the conclusion that the use of UAV in the process of obtaining imaging geoinformation and spatial data for planning and documentation of revitalisation work may be practical mode near-real-time. It replaces the previously used laborious and lengthy process to update data while ensuring their detail and accuracy.